1997
DOI: 10.21273/horttech.7.2.149
|View full text |Cite
|
Sign up to set email alerts
|

In-row Spacing Affects Machine-harvested Jalapeno Pepper

Abstract: Field studies were conducted in 1991 and 1992 to evaluate the effect of in-row spacing on machine-harvested jalapeno pepper (Capsicum annuum L.) yield and plant characteristics. In 1991, `TAM Mild Jalapeno-1' (TAMJ1) and `Jalapeno-M' (JM) were planted at 4-, 8-, 12-, and 16-inch (10-, 20-, 30-, 40-cm) in-row spacings and, in 1992, TAMJ1 was planted at 3-, 6-, 9-, and 12-inch (7.5-, 15-, 22.5-, 30-cm) spacings. Total marketable yield increased linearly for JM (in 1991), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The distribution of yield over the in-row spacing seems to indicate that 'Pace105' responded more like bell pepper to spacing (Locascio and Stall, 1994;Russo, 1991) than to other types of peppers (Decoteau and Graham, 1994;Kahn et al, 1997;Leskovar and Boales, 1995;Motsenbocker, 1996;Motsenbocker et al, 1993Motsenbocker et al, , 1997. The producer, using 'Pace105', has the option of either using fewer plants on the same amount of land or more plants on less land without much reduction of quantity or quality of yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of yield over the in-row spacing seems to indicate that 'Pace105' responded more like bell pepper to spacing (Locascio and Stall, 1994;Russo, 1991) than to other types of peppers (Decoteau and Graham, 1994;Kahn et al, 1997;Leskovar and Boales, 1995;Motsenbocker, 1996;Motsenbocker et al, 1993Motsenbocker et al, , 1997. The producer, using 'Pace105', has the option of either using fewer plants on the same amount of land or more plants on less land without much reduction of quantity or quality of yield.…”
Section: Discussionmentioning
confidence: 99%
“…Mississippi Sport peppers (all C. annuum L.), fresh pod yields decreased as in-row spacing increased with some of the highest yields occurring at the closest spacing (Decoteau and Graham, 1994;Kahn et al, 1997;Leskovar and Boales, 1995;Motsenbocker, 1996;Motsenbocker et al, 1993). However, total marketable yields for the pungent jalapeño peppers 'TAM Jalapeño 1' and 'Jalapeño M' were unaffected by varying in-row plant spacings from 10.2 to 40.6 cm (Motsenbocker et al, 1997). Increasing in-row spacing of bell pepper (C. annuum L.) plants did not consistently improve yield (Russo, 1991), and Locascio and Stall (1994) reported that increasing in-row spacing of bell pepper increased yield.…”
mentioning
confidence: 97%
“…Total marketable yields of specific pungent jalapeño cultivars were unaffected by increasing in-row spacing. 25 Increasing in-row spacing of bell pepper plants did not consistently improve yield 26 ; however, Locasio and Stall 27 reported an increased yield as a result of increasing in-row spacing.…”
Section: Introductionmentioning
confidence: 94%